Permafrost warming along the Mo'he-Jiagedaqi section of the China-Russia crude oil pipeline - Wang Fei; Li Guo-yu; Ma Wei; Mao Yun-cheng; Mu Yan-hu; Serban, Mihaela; Cai Yong-jun (Journal of Mountain Science, 2019)
The permafrost along the China-Russia Crude Oil Pipeline (CRCOP) is degrading since the pipeline operation in 2011. Heat dissipated from the pipeline, climate warming and anthropogenic activities leads to permafrost warming. The processes of permafrost warming along the CRCOP were studied based on the monitoring of air and soil temperatures, and electrical resistivity tomography (ERT) surveys. Results show that: (1) the mean annual air temperature (MAAT) in permafrost regions along the CRCOP increased with a rate of 0.21 degrees C/10a-0.40 degrees C/10a during the past five decades; (2) the mean annual ground temperature (MAGT, at -15 m depth) of undisturbed permafrost increased by 0.2 degrees C and the natural permafrost table remained unchanged due to the zero-curtain effect; (3) permafrost surrounding the uninsulated pipeline right-of-way warmed significantly compared with that in a natural site. During 2012-2017, the MAGT and the artificial permafrost table, 2 m away from the pipeline centerline, increased at rates of 0.063 degrees C/a and 1.0 m/a. The thaw bulb developed around the pipe and exhibits a faster lateral expansion; (4) 80-mm-thick insulation could reduce the heat exchange between the pipeline and underlying permafrost and then keep the permafrost and pipe stable. The MAGT and the artificial permafrost table, 4.8 m away from the center line of the pipeline, increased by 0.3 degrees C/a and 0.43 m/a, respectively. Due to the heat disturbance caused by warm oil, the degradation of wetland, controlled burn each autumn and climate warming, the permafrost extent reduced and warmed significantly along the CRCOP route. Field observations provide basic data to clarify the interactions between CRCOP and permafrost degradation and environmental effects in the context of climate change.